Minecraft Mods programming : absolute beginner's guide - Cadenhead, Rogers (Absolute beginner's guide (Indianapolis, Ind.), 2015)
Part I. Java from the ground up -- Dig into Minecraft programming with Java -- Use NetBeans for Minecraft programming -- Create a Minecraft Mod -- Start writing Java programs -- Understand how Java programs work -- Store and change information in a Mod -- Use strings to communicate -- Use conditional tests to make decisions -- Repeat an action with loops -- Store information with arrays -- Part II. The world of Java objects -- Create your first object -- Describe what your object is like -- Make the most of existing objects -- Store objects in data structures -- Handle errors in a Mod -- Create a threaded Mod -- Read and write files -- Part III. Create killer Minecraft Mods: Spawn a Mob -- Make one Mob Ride another -- Take a census of Mobs and villages -- Transmute materials in an inventory -- Dig a giant hole -- Chop down a forest of trees -- Respond to events in the game -- Display a Mob's health during combat -- Make a world change over time -- Befriend the God of lightning.